(untitled) (Transport systems and technologies, 2019)
Abstract. In this article the modern state of railway transport and carriage economy is characterized, the main problems and ways of their development are determined. The existing methods of repairing wagons - stationary and flow - are analyzed. The main features, advantages and disadvantages of these methods are determined. The necessity of introduction of industrial methods of repair, namely the use of flexible flow lines, is substantiated. It is determined that construction of new generation wagon repair companies, which will be adapted for the repair of each specific wagon with the use of flexible flow lines, is the basis for further development of the carriage economy. The basic requirements to the new generation of car repair enterprises are substantiated, such as improving the quality of car repairs, reducing the time spent in repairing cars, and creating conditions for the constant growth of labor productivity. It has been determined that for the introduction of high-performance industrial repair methods, such as flexible flow lines, the necessary condition is the possibility of moving wagons between specialized positions, which are exclusively intended for a certain amount of work and equipped with special technological equipment. The asynchronous flexible flow of repairs of wagons is an effective stage in the development of stream repair production, which can be created on the basis of the transformation of classical flow-conveyor lines due to changes in their structure and ties between the elements. It has a higher level of systematic than existing current-pipelines and can significantly expand the range of types of repaired cars and make the transition from one-subject specialization to multi-purpose, which includes repair of not only different types of cars, but also different types of repairs (depot , capital). The concept of flexibility and asynchronous flow is defined. Asynchronous flow indicates that wagons move from one repair position to another not all simultaneously at regular intervals, but gradually as needed and possible. Flow flexibility is an integral concept that characterizes the possibility of a quick transition to output of another type size and model. When applying a flexible flow, where there is some transport freedom and the potential for choosing the route of carriage along the flow positions, the throughput is significantly increased, and the simple carriage in the repair is reduced.